2013
DOI: 10.1017/s1751731112002339
|View full text |Cite
|
Sign up to set email alerts
|

Response of piglets to the standardized ileal digestible isoleucine, histidine and leucine supply in cereal–soybean meal-based diets

Abstract: Improving the amino acid (AA) profile of the diet by using L-Lys, L-Thr, DL-Met, L-Trp and L-Val helps to reduce the dietary CP content, thereby reducing nitrogen excretion while maintaining the performance of pigs. Valine is the fifth limiting AA in cereal-soybean meal-based diets. The extent to which the CP content in the diet can be reduced further without compromising performance depends on the requirement of the next limiting AA. In cereal-soybean meal-based diets, Ile, His and Leu may be the limiting AAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
4
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 27 publications
3
24
4
4
Order By: Relevance
“…A Phe deficiency has a small negative impact on performance, which is similar to that observed for His and Leu deficiencies, while the effect of a Tyr is very small. This contrasts with the response observed for Ile and Val deficiencies (Gloaguen et al, 2013).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…A Phe deficiency has a small negative impact on performance, which is similar to that observed for His and Leu deficiencies, while the effect of a Tyr is very small. This contrasts with the response observed for Ile and Val deficiencies (Gloaguen et al, 2013).…”
Section: Discussioncontrasting
confidence: 95%
“…This value is much lower than that proposed by current standards (NRC, 1998 and2012;BSAS, 2003). In a cereal-soybean meal-based diet, the Ile, His, and Leu supply may become limiting for growth before Phe and Tyr when the CP content is reduced (van Milgen et al, 2012;Gloaguen et al, 2013). Therefore, with the currently available crystalline AA (L-Lys, L-Thr, DL-Met, L-Trp, and L-Val), it is unlikely that dietary Phe becomes limiting for growth in practical low CP diets.…”
Section: Discussionmentioning
confidence: 99%
“…The AIC, which was used to evaluate the adequacy of the models, showed that the quadratic-function model was an appropriate model for estimating the Leu requirement. The quadratic-function analysis revealed that the SID Leu : Lys level required to optimise growth was, on average, 108%, which is markedly higher than the estimates of 102% obtained by Gloaguen et al (2013a) and 93% obtained by Soumeh et al (2015) and is also higher than the estimate of 100% recommended by the NRC (2012). The observed effects of the high-Leu diets on FI and growth can probably be explained by the recently described anorexigenic effect of Leu (Cota et al, 2006;Wiltafsky et al, 2010;Wessels et al, 2016) and the finding that an excessive consumption of Leu may induce its own degradation via an irreversible oxidative-decarboxylation reaction by the BCKDH complex, which limits growth (Wiltafsky et al, 2010;Wessels et al, 2016).…”
Section: Discussionmentioning
confidence: 56%
“…However, data from more recent studies provide contradictory results. In 2013, Gloaguen et al (2013a and2013b) estimated the Leu requirement of piglets based on a curvilinear-plateau model and suggested that 102% was an appropriate SID Leu : Lys level to maximise the daily gain of piglets fed a low-CP diet. However, Soumeh et al (2015) found that a SID Leu : Lys level of 93% was sufficient to maximise growth in 8 to 12 kg female piglets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation